REPRESENTATION OF OPPRESSION AGAINST YOUTHIN A MILD TELEVISION ADVERTISEMENTS - Wina Widianingsih, - (2011)
Television advertisement is an interesting media to analyze. Television advertisement becomes more interesting by the existence of cigarette advertisements. Numbers of cigarette advertisements often present the analogy of social issues both in critical and entertaining visualizations. One cigarette advertisement which represents the analogy of social issues in a critical and entertaining visualization is the A Mild cigarette television advertisements. A Mild's cigarette television advertisements constructs the analogy of social issues occurred through an extraneous example of the oppression against youth in a critical yet, entertaining visualizations. Thus, this study entitled "REPRESENTATION OF OPPRESSION AGAINST YOUTH IN A MILD TELEVISION ADVERTISEMENTS" is aimed at investigating how are the A Mild television advertisements "Tanya Kenapa" theme "Siapa Muda Dipandang Sebelah Mata" and "Belum Tua Belum Boleh Bicara" versions represent the oppression against youth. The study used a qualitative descriptive approach framed in semiotics analysis, especially Barthes's orders of signification as a tool to analyze the denotative and connotative meaning of visual representation in each advertisement. The result of this study shows that the oppression against youth is represented through the visual elements (especially the old actors' gesture) of some related scenes in both advertisements which connote that youth is being oppressed and demoralized by the old people.